The history of the flute in jazz, basic techniques, and how jazz and improvisation can inform a classical performance - Rodriguez, Florida (Kansas State University, 2018)
This report covers a history of the flute in jazz music as well as the advancement of the flute in jazz, starting from the late 1920s. The lives of jazz flute pioneers Alberto Socarrás, Wayman Carver, Herbie Mann, Hubert Laws, and Ali Ryerson are discussed, as well as their contributions to the history of jazz flute. Basic jazz techniques such as improvisation are broken down and explained for classically trained flutists and others who have an interest in playing jazz music but do not know where to begin. This report also discusses how practicing these techniques can further aid in preparing a classical performance. Examples included in this report are excerpts from Mozart’s Concerto in D Major for flute and Mike Mower’s Sonata Latino.
Keywords: Beginner improvisation; History of the flute in jazz; How to start improvising on flute; How does practicing jazz flute help with classical flute music